(3JbfjGJ GdEYdGe (B/s - (3jYbhH, WGdH s ((3ShDjG (B:s (3OGQ UaMGJ ddfTQ h GdJhRjY ,s, 2012)
(3Gf gPG GdcJGH djS Shi eMGhdI LGOI deYQaI JbfjGJ GdGYdGe h gh GgejJg ddeTJZdjf aj GdGYdGe s
Keywords: (3GdOQGeG s; (3GdUhJjGJs; (3GdePjYs; (3af GdGdbGAs